A method for assessing the accuracy of surgical technique in the correction of astigmatism. Issue 12 (December 1992) - Kaye, S. B.; Campbell, S. H.; Davey, K.; Patterson, A.
Abstract : Surgical results can be assessed as a function of what was aimed for, what was done, and what was achieved. One of the aims of refractive surgery is to reduce astigmatism; the smaller the postoperative astigmatism the better the result. Determination of what was done--that is, the surgical effect, can be calculated from the preoperative and postoperative astigmatism. A simplified formulation is described which facilitates the calculation (magnitude and direction) of this surgical effect. In addition, an expression for surgical accuracy is described, as a function of what was aimed for and what was achieved.